A novel approach to developing effective maritime regulations: The case of LNG cargo filling limits. (2nd October 2022) - Ha, Seung-Man; Jeong, Byongug; Park, Chybyung
ABSTRACT: This paper introduces a novel approach to resolving a part of the fundamental problems encountered in the current practice of maritime regulatory frameworks. The novelty of the proposed method lies in a detailed and structured process that can examine and verify the appropriateness of a particular regulation in terms of integrating economic, environmental and safety impacts. Through its built-up database of approximately 440 LNG carriers in the world, the excellence of the proposed approach has been demonstrated by investigating the suitability of a controversial regulation related to the LNG cargo filling limit set forth in " the International code for the construction & Equipment of Ships carrying liquefied gases in Bulk." A series of case studies have confirmed 169 LNG carriers currently are subjected to being placed under this issue. In this study, we identified ships' key characteristics which would contribute to the increase in total costs associated with economic, environmental and safety impacts and presented the threshold between the opportunity costs and the severity of the regulation. The research findings have provided a managerial insight that may increase the reliability of maritime regulations by applying this pragmatic/analytical regulatory framework model developed in this research.